Penerapan Mikro Buble Ozon Pada Proses Produksi Edamame Beku Di PT. Tagani Sukses Makmur: Paket teknologi MNBO pada pencucian edamame - Bakri, Abi Bakri; Hariono, Budi; Kurnianto, Muhammad Fathoni; Azhar, Faruq Avero (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This manuscript is a written work from a community service activity, namely a collaborative package of activity implementers from the Jember State Polytechnic with Industrial partners PT. Tagani Sukses Makmur. The innovation of Micro Bubble Ozone (MBO) technology is a research result that can be applied to the edamame soybean washing process because this ozone technology can decontaminate microorganisms and reduce pesticide residues in edamame soybeans. This activity includes a Reverse Osmosis water filter technology package and MBO washing equipment, assistance with tool operation; training in the frozen edamame production process referring to SOPs according to GMP and HACCP. This manuscript is our latest written work, it has never been published in other journals before and I really hope that this manuscript can be published in Komunita, a journal of Community Service and Empowerment